Catalogue of the mite family Tydeidae (Acari: Prostigmata) with the world key to the species - Silva, Guilherme Liberato Da; Metzelthin, Maicon Henrique; Silva, Onilda Santos Da; Ferla, Noeli Juarez (Zootaxa, 2016)
Members of the Tydeidae are cosmopolitan, soft-bodied, striated or reticulated mites that are reported to be mainly phytophages, mycophages, pollenophages, insect parasites or scavengers. This catalogue includes 328 species belonging to 30 genera, and their distributions and type habitat. Until now, Brachytydeus comprises the largest number of species with 200, followed by Tydeus, with 50 species, and Pretydeus and Pseudolorryia, with 12 species each. An updated list of the Tydeidae (Acari: Prostigmata), a world key to the species and data on the zoogeographical distribution of the species are presented.